(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Effective collaboration between lab technicians and nurses is essential for providing high-quality patient care. However, several challenges such as communication barriers, differing priorities, and resource constraints often hinder this collaboration. This paper explores these challenges and proposes solutions to address them. Key strategies include implementing regular interdisciplinary meetings, fostering mutual understanding of roles and priorities, advocating for resource optimization, offering interdisciplinary education programs, establishing quality assurance mechanisms, and leveraging technology for seamless information exchange. By addressing these challenges, healthcare organizations can enhance collaboration between lab technicians and nurses, leading to improved patient outcomes and healthcare delivery